2015
DOI: 10.1002/gps.4380
|View full text |Cite
|
Sign up to set email alerts
|

Patients' and carers' experiences of UK memory services

Abstract: Patients and carers had very good experiences of memory services overall whether they had standard or excellent accreditation. However, 'excellent' services were consistently better on a number of factors. This provides further support that the accreditation process is an important indicator of the quality of memory services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…19 Approximately a third of UK services are accredited, 20 and we focused on these as they represent current UK best practice. 19 Approximately a third of UK services are accredited, 20 and we focused on these as they represent current UK best practice.…”
Section: Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Approximately a third of UK services are accredited, 20 and we focused on these as they represent current UK best practice. 19 Approximately a third of UK services are accredited, 20 and we focused on these as they represent current UK best practice.…”
Section: Surveysmentioning
confidence: 99%
“…In 2009, the UK Royal College of Psychiatrists established the Memory Services National Accreditation Programme (MSNAP). 19 Approximately a third of UK services are accredited, 20 and we focused on these as they represent current UK best practice. We developed a survey based on a literature review and the NICE and EAPC guidelines, 13,14 delivered through the programme Opinio.…”
Section: Surveysmentioning
confidence: 99%
“…[12][13][14][15][16] The aims of this study were: to describe the change in health related quality of life (HRQL) over the first 6 months after first referral to MAS; to assess whether patient characteristics, including diagnosis, are associated with changes in HRQL; and to determine if use of antidementia drugs and non-pharmacological post-diagnostic therapies are associated with improved HRQL among those patients diagnosed with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies exploring the experiences of patients and their family members in an MC report that they initially felt stressed and unnerved and that they often did not know what to expect of their visit to the clinic (Mastwyk et al, 2016). However, in both qualitative and quantitative studies, the overall experience were found to be more positive than negative, and patients and family members were often satisfied with the diagnostic process (Cahill et al, 2008;Foreman et al, 2004;Hailey et al, 2016;Hodge et al, 2013;Park et al, 2018).…”
Section: Introductionmentioning
confidence: 99%